2010
DOI: 10.1080/08927014.2010.501895
|View full text |Cite
|
Sign up to set email alerts
|

SOS involvement in stress-inducible biofilm formation

Abstract: Bacterial biofilm formation can be induced by antimicrobial and DNA damage agents. These agents trigger the SOS response, in which SOS sensor RecA stimulates auto-cleavage of repressor LexA. These observations lead to a hypothesis of a connection between stress-inducible biofilm formation and the RecA-LexA interplay. To test this hypothesis, three biofilm assays were conducted, viz. the standard 96-well assay, confocal laser scanning microscopy, and the newly developed biofilm-on-paper assay. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 47 publications
0
58
0
Order By: Relevance
“…As a result, these strains become adapted to survive in the stressful niche of CF patient lungs (45). It is likely that replication-inhibiting antibiotics enhance chronic biofilm infections through the SOS response; however, it is possible that SOS response suppression acquired by resistance to DNA-inhibiting antibiotics may also play a role (7,55). Overall, intact SOS and active DNA repair systems seem to be essential for biofilm formation under drug treatment in P. aeruginosa.…”
Section: Figmentioning
confidence: 99%
“…As a result, these strains become adapted to survive in the stressful niche of CF patient lungs (45). It is likely that replication-inhibiting antibiotics enhance chronic biofilm infections through the SOS response; however, it is possible that SOS response suppression acquired by resistance to DNA-inhibiting antibiotics may also play a role (7,55). Overall, intact SOS and active DNA repair systems seem to be essential for biofilm formation under drug treatment in P. aeruginosa.…”
Section: Figmentioning
confidence: 99%
“…During SOS, premature cell division is prevented, and genes for DNA damage repair are induced. SulA, the SOS gene product, inhibits cell division by binding to FtsZ to block septum formation until the DNA damage has been repaired (Higashitani et al, 1995;Gotoh et al, 2010). Although the filamentation protects daughter cells from receiving damaged copies of the bacterial chromosome, the filamentous phenotype can also involve other programmes that are designed to promote bacterial survival (Justice et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the activation of the SOS response is involved in the adherence to abiotic surfaces by E. coli (Hoffman et al, 2005;Linares et al, 2006;Gotoh et al, 2010), Vibrio cholerae (Hung et al, 2006;Gotoh et al, 2010) and Mycobacterium avium (Geier et al, 2008;Gotoh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have attempted to explain the large amount of hypermutators in a bacterial population known to readily form biofilms. Bacterial biofilm formation can be induced by DNA damaging agents (involved in mutations) triggering the SOS response, through a connection between stress-inducible biofilm formation and the RecA-LexA interplay [49]. Damaging agents have been described, including silver nanoparticles used for their antibacterial properties [50], oxidative product created by other bacteria present in the biofilm (i.e.…”
Section: Hypermutation and Biofilm Formation 72mentioning
confidence: 99%